Faces of Béxar : early San Antonio and Texas. - Teja, Jesús F. de la; Teja, Jesâus F. de la ([Place of publication not identified] Texas A & M University Press, 2016)
Faces of Bexar showcases the finest work of Jesús F. de la Teja, a foremost authority on Spanish colonial Mexico and Texas through the Republic. These essays trace the arc of the author's career over a quarter of a century. A new bibliographic essay on early San Antonio and Texas history rounds out the collection, showing where Tejano history has been, is now, and where it might go in the future. For de la Teja, the Tejano experience in San Antonio is a case study of a community in transition, one moved by forces within and without. From its beginnings as an imperial outpost to becoming the center of another, newer empire--itself in transition--the social, political, and military history of San Antonio was central to Texas history, to say nothing of the larger contexts of Mexican and American history. Faces of Bexar explores this and more, including San Antonio's origins as a military settlement, the community's economic ties to Saltillo, its role in the fight for Mexican independence, and the motivations of Tejanos for joining Anglo Texans in the struggle for independence. Taken together, Faces of Bexar stands to be a milestone in the growing literature on Tejano history.
Preface -- Spanish colonial Texas -- "A fine country with broad plains -- the most beautiful in New Spain" : views of land and nature in colonial San Antonio -- Forgotten founders : the military settlers of eighteenth-century San Antonio de Bexar -- "To the last drop of our blood" : defending king and empire in San Antonio -- The Saltillo Fair and its San Antonio connections -- Why Urbano and Maria Trinidad can't get married : social relations in late colonial San Antonio -- "Buena gana tenia de ir a jugar" : the recreational world of early San Antonio, Texas, 1718-1845 -- Discovering the Tejano community in "early" Texas -- Rebellion on the frontier -- The colonization and independence of Texas : a Tejano perspective.
English.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Spanish Americans -- Texas -- San Antonio -- History; Mexican Americans -- Texas -- San Antonio -- History; Américains d'origine espagnole -- Texas -- San Antonio -- Histoire; Américains d'origine mexicaine -- Texas -- San Antonio -- Histoire; HISTORY -- Historiography; HISTORY -- United States -- State & Local -- Southwest (AZ, NM, OK, TX); SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; SOCIAL SCIENCE -- Minority Studies; Mexican Americans; Spanish Americans; Texas; Texas -- San Antonio; To 1846; History